The need of an HR consultancy organization for employee recruitment process in Bangladesh. (a study on “grow n excel”) - Zohora, Fatema Tuz (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.